2021
DOI: 10.3389/fcell.2021.749924
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Mesenchymal Stromal/Stem Cell Marker Meflin/Islr in Cancer Fibrosis

Abstract: Fibroblasts synthesise the extracellular matrix (ECM) such as collagen and elastin, the excessive accumulation of which can lead to fibrosis and organ dysfunction under pathological conditions. Cancer-associated fibroblasts (CAFs) are major constituents of the tumour microenvironment (TME) that accompany the desmoplastic reaction responsible for anti-cancer treatment resistance. Thus, it is important to dissect the roles of CAFs in the TME to develop new therapeutic strategies for refractory cancers. Recent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 74 publications
(129 reference statements)
0
24
1
Order By: Relevance
“…Our group recently focused on another protein, Meflin, which is specifically expressed in CAFs in both human and mouse PDAC [ 26 , 28 , 29 , 38 ]. It is a glycosyl-phosphatidylinositol-anchored protein encoded by the gene immunoglobulin superfamily containing leucine-rich repeats ( ISLR ), which is also secreted into media containing cultured fibroblasts [ 29 , 39 ].…”
Section: Current Understanding About Rcafs In Pdacmentioning
confidence: 99%
“…Our group recently focused on another protein, Meflin, which is specifically expressed in CAFs in both human and mouse PDAC [ 26 , 28 , 29 , 38 ]. It is a glycosyl-phosphatidylinositol-anchored protein encoded by the gene immunoglobulin superfamily containing leucine-rich repeats ( ISLR ), which is also secreted into media containing cultured fibroblasts [ 29 , 39 ].…”
Section: Current Understanding About Rcafs In Pdacmentioning
confidence: 99%
“…Cancer-associated fibroblasts (CAFs) play a pivotal role in tumor progression. CAFs enhance cancer cell proliferation [ 54 ], angiogenesis and lymphangiogenesis [ 55 ], ECM remodeling, immune cell recruitment [ 56 ], invasion and metastasis via cytokine and chemokine secretion [ 57 , 58 , 59 , 60 , 61 , 62 ]. CAFs are a highly heterogeneous subpopulation of stromal cells in TME, originating from different precursors, including resident tissue fibroblasts, bone marrow mesenchymal stem cells, hematopoietic stem cells, epithelial cells and endothelial cells [ 63 , 64 , 65 ].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…Tumor cells are responsible for recruiting stromal cells (myofibroblasts) and immune cells to initiate multi-stage progression. Fibroblasts are involved in extracellular matrix formation due to the synthesis of structural proteins, e.g., integrins, collagen, or elastin [45,46]. Cho et al showed the myofibroblast impact on fibronectin remodeling through paracrine communication with tumors [47]., A fibroblast subtype crucial for tumor progression include cancer associated fibroblasts (CAFs) developed from myofibroblasts.…”
Section: Tumor Stromamentioning
confidence: 99%
“…Nevertheless, high tumor mutational burden, which is typical for smokers, is connected with better "visibility" of tumors for immune cells [64]. Tumor-infiltrated immune cells may include cancer-infiltrated cytotoxic T cells (CTLs), memory T cells (CD 45 RO + ), regulatory T cells (CD4 + CD25 + ), tumor-infiltrated macrophages type M1 and/or M2, and dendritic cells. The infiltration location may appear in the tumor core or its marginal side.…”
Section: Immunology Of Lung Cancer Tumormentioning
confidence: 99%